Roll-out of male circumcision as an intervention against HIV in a South African community - (:unkn) unknown (My University, 2013)
The protective effect of male circumcision (MC) on HIV heterosexual acquisition among men was demonstrated in three randomized controlled trials conducted in Southern and Eastern Africa, and its roll-out has been recommended by the WHO and UNAIDS as an important complementary component of HIV prevention strategies in high incidence communities with low rates of MC. However, the scale-up of MC in communities where it is not a social norm raises several challenges in regards to its acceptability, its implementation, its uptake, and its impact on sexual behavior as well as knowledge, attitudes and practices about MC. The ANRS 12126 Bophelo Pele project was implemented following the international recommendations in the community of Orange Farm (South Africa), site of the first MC randomized controlled trial, and target community of this strategy. Research activities conducted to evaluate the project show that the roll-out of MC is acceptable and can be implemented quickly in limited resources settings according to international recommendations in a safe and cost-effective manner. MC uptake among uncircumcised men is satisfactory. In addition, three years after project implementation, no difference in sexual behavior between circumcised men and uncircumcised men and between female partners of circumcised and uncircumcised men was detected, although knowledge and attitudes about MC and its association with HIV could be improved. MC as an HIV prevention method in hyperendemic communities is a promising strategy which can have a considerable impact on the epidemic in Eastern and Southern Africa.
Keywords: African Research